(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The use of medicinal plants in traditional healthcare practices presents an exciting opportunity for novel antimicrobial agents. This research study investigated the antibacterial properties of Rumex nepalensis, a common ethnomedicinal plant, against Staphylococcus aureus, which is a clinically significant pathogen that causes a wide variety of human infections. The crude leaf extracts of R. nepalensis were tested using the agar well diffusion test. and the results showed significant inhibitory activity against S. aureus. Following phytochemical screening, compounds were identified using Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS). Seven of the twelve bioactive compounds that were found - Chrysophanol, Hastatusides A, L-Phenylalanine, Schisandrin C, Cis-p-Coumaric acid, Pinoresinol, and Βeta-Caryophyllene - met the requirements for drug-likeness and were chosen for further analysis. The interaction of these drugs with S. aureus virulence-associated protein targets, including Gamma Haemolysin, Exfoliative Toxin, Lysostaphin-type Metalloendopeptidase, and Toxic Shock Syndrome Toxin-1, was evaluated using In-Silico Molecular Docking experiments. Strong binding affinities were shown by Chyrsophanol with all four targets, notably with Exfoliative Toxin, Lysostaphin, and Toxic Shock Syndrome Toxin. These results suggest that Chrysophanol is a potential bioactive component that supports R. nepalensis antibacterial action.